1998
DOI: 10.1111/j.1440-1746.1998.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum N‐acetylglucosaminyltransferase III activities in hepatocellular carcinoma

Abstract: N-Acetylglucosaminyltransferase III (GnT III) catalyses the addition of N-acetylglucosamine through a beta 1-4 linkage to the mannose of the trimannosyl core, resulting in conversion of the concanavalin A (Con A)-reactive glycan into a non-reactive state. In this study, we measured GnT III activity to evaluate its diagnostic efficacy and its therapeutic effect on hepatocellular carcinoma (HCC). Concanavalin A-non-reactive fraction of serum transferrin (Tf) was also determined since the sugar chains of Tf are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…We also showed that GnT-III expression levels in HBx-transfected cells is higher than that in hepatocarcinoma HepG2 cells as well as GnT-IIItransfected cells, indicating that HBx induces GnT-III expression with strong GnT-III promotor activity. Therefore, this finding supports several studies which show that GnT-III expression may be involved in the development of HCC (23,25). Unfortunately, this study did not determine the precise promotor region involved in the activation for GnT-III expression by HBx because of the limitation of the comprehensive properties of the GnT-III promoter region (38,39), but this is the first report that HBx transactivates GnT-III expression.…”
Section: Fig 5 Characterization Of Immunoprecipitated Apob Fromsupporting
confidence: 80%
“…We also showed that GnT-III expression levels in HBx-transfected cells is higher than that in hepatocarcinoma HepG2 cells as well as GnT-IIItransfected cells, indicating that HBx induces GnT-III expression with strong GnT-III promotor activity. Therefore, this finding supports several studies which show that GnT-III expression may be involved in the development of HCC (23,25). Unfortunately, this study did not determine the precise promotor region involved in the activation for GnT-III expression by HBx because of the limitation of the comprehensive properties of the GnT-III promoter region (38,39), but this is the first report that HBx transactivates GnT-III expression.…”
Section: Fig 5 Characterization Of Immunoprecipitated Apob Fromsupporting
confidence: 80%
“…This enzyme was determined in hepatic nodules of humans and rats and the GnT-III activity in these nodules were shown to be significantly higher in contrast to its surrounding and the control liver [70][71][72]. These studies suggest a possible correlation between the GnT-III activity and the precancerous stage of hepatocarcinogenesis.…”
Section: N-acetylglucosaminyltransferase IIImentioning
confidence: 98%
“…The activity of GnT-III in serum samples of HCC patients was determined by HPLC and it was significantly higher up-regulated in these patients in contrast to patients showing liver cirrhosis, chronic hepatitis and healthy controls. The GnT-III activity could be useful in HCC treatment follow-up because GnT-III activity is significantly reduced in HCC following percutaneous ethanol infection therapy and/or transcatheter arterial chemoembolization [71].…”
Section: N-acetylglucosaminyltransferase IIImentioning
confidence: 99%
“…These alterations in the glycosylation of proteins were extensively studied in human tissues and especially in serum [13,15,2527]. Other described alterations of glycans include increased branching, sialylation, agalactosylated glycans or polylactosamine chains [16,28,29]. …”
Section: Introductionmentioning
confidence: 99%